Development of a hybrid solar wind turbine for sustainable energy storage - Soon , Ching Chun (2015)
This thesis presents the design of hybrid solar wind turbine system for the power generation system by utilising both solar and wind renewable energy to the domestic household in the remote area which is unable to connect to the grid. The study was started by investigating the availability of both solar and wind energy in the desired location which is southern region of Malaysia. The design of wind turbine is modelling by Solidworks computer aided design (CAD) software. The computational fluid dynamics (CFD) is conducted by Solidworks Flow Simulation. The method of virtual wind tunnel simulation was adopted for wind turbine internal flow analysis with several of wind speed, in order to obtain the result of wind turbine performance in various levels of wind data. The data of solar radiation and wind speed were collected from the Malaysian Meteorological Department, then system configuration analysis done by simulation tool, HOMER. The basic requirement of electric primary load is determined in 12.06 kW per day for single household which is included the essential load demand such as lighting, computer and household appliance. The optimization analysis is conducted for generating most feasible system configuration and determines the quantity of components in the hybrid energy system, in order to meet the load demand of household and achieve the autonomy power supply with storing excess power generated in batteries storage for the sustainable energy storage.